(untitled) (International Journal of Environmental Sciences, 2025)
This study investigates the mechanical and microstructural characteristics of Al319 aluminum alloy reinforced with varying weight percentages (3.5–9.5 wt.%) of dry fly ash, fabricated using the stir casting technique. The influence of fly ash reinforcement on tensile strength, microstructural evolution, and fracture behavior was systematically analyzed. The tensile testing results revealed that Sample 2, containing 5.5 wt.% fly ash, exhibited the highest ultimate tensile strength (157.74 MPa), surpassing the base Al319 alloy (140 MPa). The enhancement in mechanical properties was attributed to grain refinement and uniform dispersion of reinforcing particles. However, excessive fly ash content (7.5–9.5 wt.%) led to a decline in tensile strength due to microstructural defects and increased porosity. The stress-strain behavior indicated that optimized reinforcement contributes to improved strength and ductility. Samples with increased fly ash content exhibited brittle fracture features based on scanning electron microscopy (SEM) analysis, whereas mixed-mode failure was noted in the optimally reinforced sample. Balancing strength with toughness, these are the applications and its implications of fly ash-reinforced Al319 composites in structural and automotive applications.